Peran Kecerdasan Emosional Dalam Meningkatkan Hafalan Al-Qur’an di SMP Islam Terpadu Al-Ishlah Kabupaten Maros - Muh. Rogib Fauzy; Nur Amri Ramadhan; Rasyid Ridha; Sam’ un Mukramin (Tarbiya Islamica, 2023)
Memorizing the Qur'an does not only use intellectual intelligence but also requires emotional intelligence. Students who excel academically do not necessarily have a lot of Al-Qur'an memorization. Memorizing the Qur'an is influenced by motivation, patience and seriousness of students. This study aims to express the role of emotional intelligence in improving the memorization of the Qur'an at the Integrated Islamic Junior High School Al-Ishlah Maros Regency. A total of 9 samples were involved using purposive sampling techniques and data collection techniques using observation and interviews. Data analysis used qualitative data analysis techniques with a thematic approach. This research contributes to the understanding of the role of emotional intelligence in improving the memorization of the Qur'an. Based on the results of the study, it can be concluded that emotional intelligence has an important role in improving memorization of the Qur'an. Students who have good emotional intelligence will have high motivation, patience, ability to control emotions and seriousness in memorizing the Qur'an.